2-Phosphine-pyridine-N-oxide palladium and nickel catalysts for ethylene polymerization and copolymerization with polar monomers. (24th April 2020) - Zhang, Yixin; Jian, Zhongbao
Abstract: A new family of [P, O] late transition metal catalysts, namely 2-phosphine-pyridine- N -oxide palladium complexes Pd1 ~Pd4 {[κ 2 ( P, O )-2-Ar2 P -6-R-(C5 H3 N O )]PdMeCl} (Pd1 : Ar = Ph, R = H; Pd2 : Ar = 2-MeO-C6 H4, R = H; Pd3 : Ar = Ph, R =  t Bu; Pd4 : Ar = 2-MeO-C6 H4, R =  t Bu) and nickel complexes Ni1 ~Ni4 {[κ 2 ( P, O )-2-Ar2 P -6-R-(C5 H3 N O )]Ni(allyl)}[BArF] (Ni1 : Ar = Ph, R = H; Ni2 : Ar = 2-MeO-C6 H4, R = H; Ni3 : Ar = Ph, R =  t Bu; Ni4 : Ar = 2-MeO-C6 H4, R =  t Bu) and Ni5 {[κ 2 ( P, O )-2-Ph2 P -6- t Bu-(C5 H3 N O )]2 Ni(allyl)}[BArF], was synthesized and comprehensively characterized by NMR spectroscopy, single-crystal X-ray diffraction, and elemental analysis. These new [P, O] palladium and nickel catalysts were evaluated for the (co)polymerization of ethylene. Among the synthesized catalysts, palladium catalysts Pd2 and Pd4 oligomerized ethylene with high activities of 10 6  g mol −1 h −1, while the nickel counterparts could polymerize ethylene in higher activities and higher polymer molecular weights, among which Ni4 preferred to afford polyethylene with the highest molecular weight. Moreover, Ni4 could catalyze the copolymerization of ethylene and biorenewable polar comonomer methyl 10-undecenoate, with the activity up to 10 5  g mol −1 h −1 and the incorporation of 0.4–1.2 mol%. Graphical abstract: Image 1 Highlights: Fully new generation P, O (2-phosphine-pyridine- N -oxide) catalysts was constructed. Pd catalysts oligomerized ethylene with high activities. Ni catalysts polymerized ethylene with higher molecular weights in high activities. Ethylene copolymerization with polar monomer was accessed by preferred Ni catalyst.